Smart Board use and Pedagogic Practices among Educators: A Case of a South African Township School - Matemera, Simbarashe (International Journal of Educational Studies, 2022)
The purpose of this study was to understand the state of smart board use and pedagogic practices among educators in a township school. Four educators participated in this case study-based research project. The study established different means in which smart boards have become central in the teaching and learning processes within the township schools. It was found that educators used the smart boards for writing, downloading and uploading multiple tasks. It was further established that smart boards were making teaching interesting. In this regard, smart boards were found to equally make teaching easier in many ways. The smart board use was however found to face challenges such as resistance especially from senior educators, technical challenges such as freezing and the challenge of load shedding. The research however concluded that despite the challenges, smart boards remained an important source of ensuring transformative and pedagogical oriented teaching and learning as well as enhanced teaching and learning in poor settings such as townships. Equally, a holistic approach that targeted key aspects of schooling such as technology and educators was used to understand how new technologies such as smart boards especially for township contexts could be drawn upon in enhancing teaching and learning. A qualitative research methodology was used in which in-depth interviews as well as observations were used for data collection. The social constructivist approach was used in the discussion of the findings. This approach aided in exploring the educator practices and opinions regarding their use of smart board technologies in various subjects.